2022
DOI: 10.21037/tlcr-21-909
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-low-dose intraoperative X-ray imager for minimally invasive surgery: a pilot imaging study

Abstract: Background: With advances in surgical technology, thoracic surgeons have widely adopted minimally invasive limited-resection techniques to preserve normal tissues. However, it remains difficult to achieve in situ localization of invisible pulmonary nodules during surgery. Therefore, we proposed an in situ ultralow-dose X-ray imaging device for intraoperative pulmonary nodule localization during minimally invasive surgeries. Methods:The proposed device features a hand-held type and consists of a carbon nanotube… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…In minimally invasive surgery (MIS), the challenge deepens since access through the incision port limits visual inspection and restricts direct finger palpation and indirect palpation through a medical instrument. Besides, these methods are rarely sufficient to assess the location of the resection margins or they are still at the experimental stage [12,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In minimally invasive surgery (MIS), the challenge deepens since access through the incision port limits visual inspection and restricts direct finger palpation and indirect palpation through a medical instrument. Besides, these methods are rarely sufficient to assess the location of the resection margins or they are still at the experimental stage [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…What would be the potential benefits of integrating these concepts into radiation detectors that are directly attached to the organs? In the specific application of nuclear imaging, we hypothesise that bringing a radiation detector closer to the source would improve the signal-to-noise ratio (SNR), thereby reducing the radiation dose required to obtain high-quality images [13,20]. This would also extend the imaging while providing instantaneous feedback during surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Park et al described the use of an ultra-low-dose X-ray imager to identify lung nodules intraoperatively (16). This device is a hand-held, clamp-shaped endoscopic instrument that employs a carbon nanotube, which allows a compact design.…”
mentioning
confidence: 99%
“…The second issue with the ultra-low-dose X-ray imager is that Park et al identified lesions containing contrast media (16). In clinical practice, the insertion of a contrast agent into a lesion involves an extra procedure, which involves additional radiation exposure and procedural risks.…”
mentioning
confidence: 99%